Epidemiological and Molecular Characterization of Dengue Virus Circulating in Bhutan, 2013-2014. - Sangay Zangmo; Chonticha Klungthong; Piyawan Chinnawirotpisan; Srisurang Tantimavanich; Nathamon Kosoltanapiwat; Butsaya Thaisomboonsuk; Kelzang Phuntsho; Sonam Wangchuk; In-Kyu Yoon; Stefan Fernandez (PLOS Neglected Tropical Diseases, 2015)
Dengue is one of the most significant public health problems in tropical and subtropical countries, and is increasingly being detected in traditionally non-endemic areas. In Bhutan, dengue virus (DENV) has only recently been detected and limited information is available. In this study, we analyzed the epidemiological and molecular characteristics of DENV in two southern districts in Bhutan from 2013-2014. During this period, 379 patients were clinically diagnosed with suspected dengue, of whom 119 (31.4%) were positive for DENV infection by NS1 ELISA and/or nested RT-PCR. DENV serotypes 1, 2 and 3 were detected with DENV-1 being predominant. Phylogenetic analysis of DENV-1 using envelope gene demonstrated genotype V, closely related to strains from northern India.